Manufacturing servitisation and duration of exports in China. (6th February 2018) - Cui, Yaqiong; Liu, Bin
Abstract: In recent years, manufacturing servitisation has become a growing characteristic of global firms. Firms develop their service factors, to realise more values and increase their international competitiveness. China, as an important manufacturing centre of the world, has abundant manufacturers seeking for getting more involved in the international market. This paper makes use of detailed customs data and firm‐level data from China, to find how the servitisation in China affects the export durations of Chinese manufacturers. The results demonstrate that manufacturing servitisation input in China contributes to export performance. The service factors have become the important production factors in Chinese manufacturing enterprises. However, China is still at the primary stage of manufacturing servitisation, and Chinese manufacturing enterprises should pay more attention to the whole value chain and seek the transformation from a pure manufacturing enterprise to a service manufacturing enterprise.